2023
DOI: 10.1038/s41467-023-40221-0
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature-dependent interphase formation and Li+ transport in lithium metal batteries

Abstract: High-performance Li-ion/metal batteries working at a low temperature (i.e., <−20 °C) are desired but hindered by the sluggish kinetics associated with Li+ transport and charge transfer. Herein, the temperature-dependent Li+ behavior during Li plating is profiled by various characterization techniques, suggesting that Li+ diffusion through the solid electrolyte interface (SEI) layer is the key rate-determining step. Lowering the temperature not only slows down Li+ transport, but also alters the thermodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 61 publications
(99 reference statements)
0
33
0
Order By: Relevance
“…4d), resulting in similarly low E a-Li + values of 0.095 eV and 0.064 eV, respectively. However, the low E a-Li + for the GO-modified separator is an artifact of the Arrhenius model 20,54–56 due to the near-zero Li + flux through the GO membrane in this temperature range ( i.e. , from 10 to 60 °C).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…4d), resulting in similarly low E a-Li + values of 0.095 eV and 0.064 eV, respectively. However, the low E a-Li + for the GO-modified separator is an artifact of the Arrhenius model 20,54–56 due to the near-zero Li + flux through the GO membrane in this temperature range ( i.e. , from 10 to 60 °C).…”
Section: Resultsmentioning
confidence: 90%
“…However, the low E a-Li + for the GO-modified separator is an artifact of the Arrhenius model 20,[54][55][56] due to the near-zero Li + flux through the GO membrane in this temperature range (i.e., from 10 to 60 1C).…”
Section: Papermentioning
confidence: 92%
“…The main bottleneck of liquid batteries at low temperatures is focused on the interface, such as the difficulty of desolvation and the deterioration of the SEI conductivity. 166,167 SSBs not only face similar problems, but also suffer from more limitations from Li + conduction in the bulk phase. 55 We think that the difficulty of Li + transfer in the bulk phase is the main bottleneck.…”
Section: Discussionmentioning
confidence: 99%
“…71 Similarly, recent studies have found that the reactive kinetic barrier for the lithium deposition process was increased at low temperatures, and the Li + transport process through the SEI was slowed down, leading to an increase in polarization. 72 In contrast to room temperature, the battery CE was worse at higher temperatures. However, in the ether-based electrolyte system, the results were different from the conventional carbonate system.…”
Section: Morphology Characterizationmentioning
confidence: 99%